Dutch Batik Motifs: The Role of The Ruler and The Dutch Bussinesman - Patria, Asidigisianti Surya (Harmonia: Journal of Arts Research and Education, 2016)
Dutch Batik is the referent of batik which is made by European-Indo woman industry. It can be identified by the European pattern which is a bouquet. This research is aimed to describe the correlation between the development of Dutch Batik with the role of the Dutch government and the Dutch merchant. The library research was used during analyzing the role of the government and the merchant using the Talcott Parsonsâ functional structure theory. The batik Dutch companies were commercial oriented. It is different from real Javanese batik which had a purpose to be worn by themselves. Dutch Batik was the expression of the idea and behavior of the Dutch who lived in Indonesia. They expressed their western by using the patterns that were shown in their batik.